Anger mood detection based on face recognition and heartbeat - Mohamed, Masnani; Jusoh, Noordina Syazana; Ahmad, Ida Laila (IJERT.ORG, 2013)
Anger is one of the feeling that showing strong resentment that can be found in facial expressions, body language, physiological responses and at times in public acts of aggression. So, this project has designed to examine the existence of the individual nature of anger using facial expression and heartbeat. The objective of this project is to warn and help people to control their temper. This can prevent the bad effect towards heart rate, blood pressure, levels of adrenaline and noradrenalin and other physical effects. Matlab-Image-processing is used to analyze facial expressions while heartbeat is measured using a heartbeat detector circuit. The Graphic User Interface (GUI) indicates the angry face result while the Liquid Crystal Display states the faster heartbeat when a person is angry.